Surface treatment of carbon fibres for interfacial property enhancement in composites via surface deposition of water soluble POSS nanowhiskers. (14th February 2018) - Kafi, Abdullah; Li, Quanxiang; Chaffraix, Thomas; Khoo, Jiyi; Gengenbach, Thomas; Magniez, Kevin Jean-Claude
Abstract: This study reports for the first time the use of water soluble sulfonated octa-phenyl POSS nanowhiskers for the surface treatment for carbon fibres using simple dip-coating method. The water soluble nature of the functionalized POSS makes it appealing from a formulation perspective as it can be applied simply using an aqueous media. The synthesis of the water soluble SOP-POSS was achieved via one-step aromatic electrophilic sulfonation of octaphenyl POSS. Collective results from NMR, XPS and FTIR analysis confirmed the meta mono-substitution of all phenyl rings in the starting material with a sulfonic group, leading to its water solubility. Surface treatment of commercially oxidized and unsized carbon fibres was achieved via simple dip-coating of the fibres in an aqueous media solution containing the synthesized SOP-POSS product. After the dip-coating process, the carbon fibres are homogeneously covered with surface adsorbed SOP-POSS nanowhiskers. Physico-chemical characterization of the fibres investigated by Inverse Gas Chromatography (IGC) revealed an improvement in surface chemical homogeneity associated with a significant increase in surface oxygen contents and an overall level of surface polarity comparable to commercially sized fibres. The interfacial adhesion properties between the treated carbon fibres and an epoxy matrix were investigated by single fibre fragmentation technique. The results of the tests revealed that significant enhancement of interfacial properties was achieved as a result of a combination of physical inter-molecular interactions at the fibre-matrix interface and localized nano-mechanical strengthening of the epoxy. The outcomes of this research lay the path forward for a potential simple surface treatment of commercial carbon fibres for Interfacial property improvement in composites. Graphical abstract: Image 1 Highlights: Oxidized carbon fibers were treated via dip coating in aqueous media containing a synthesized water soluble sulfonated octa-phenyl POSS. After treatment the carbon fibers are homogeneously covered with surface adsorbed SOP-POSS nanowhiskers. An overall level of surface polarity comparable to commercially sized fibers was measured using Inverse Gas Chromatography. The interfacial adhesion properties, investigated by fragmentation technique, were found excellent and comparable to commercial fibers. This research lays the path forward for a potential simple surface treatment of commercial carbon fibers.